If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 3) = -2(x + 2) + -3 Reorder the terms: 3(3 + 2x) = -2(x + 2) + -3 (3 * 3 + 2x * 3) = -2(x + 2) + -3 (9 + 6x) = -2(x + 2) + -3 Reorder the terms: 9 + 6x = -2(2 + x) + -3 9 + 6x = (2 * -2 + x * -2) + -3 9 + 6x = (-4 + -2x) + -3 Reorder the terms: 9 + 6x = -4 + -3 + -2x Combine like terms: -4 + -3 = -7 9 + 6x = -7 + -2x Solving 9 + 6x = -7 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 9 + 6x + 2x = -7 + -2x + 2x Combine like terms: 6x + 2x = 8x 9 + 8x = -7 + -2x + 2x Combine like terms: -2x + 2x = 0 9 + 8x = -7 + 0 9 + 8x = -7 Add '-9' to each side of the equation. 9 + -9 + 8x = -7 + -9 Combine like terms: 9 + -9 = 0 0 + 8x = -7 + -9 8x = -7 + -9 Combine like terms: -7 + -9 = -16 8x = -16 Divide each side by '8'. x = -2 Simplifying x = -2
| 0=4.5c | | 5=7x+15-2x | | 28t=6(7t-6) | | 2+-15n=5(-3n+2) | | 5x-25=5x+24 | | 7b^2-6b= | | -10+0.25x=10 | | -10+0.25x=-5 | | 8+4k=-10+4k | | 4d+28=88 | | -3x^2+10x-7=0 | | 4u=37+4u | | -1550-7x=5 | | 7x^2+39x-70= | | 2n-8=7n+4+8 | | 4-(2x-3)=2(2x+1)+5 | | -2+4y=70 | | -2y=-2+x | | 7x^2-11x-6= | | 1*2+x=16 | | 3(x-1)=4x-8 | | p-2-6+12=4p-2 | | -2k+13=2m-3 | | 8b=6n-14 | | 0.2n+9=8(0.4+-1) | | -6-2y=-x | | 3x-4*5x(7)=0 | | 12-r=15 | | b+13=-5b | | 3x-11=34+28 | | 9x+7=3x-5vI | | 10x+3(8+8x)=-6(x-4) |